Implementation of Moral Education through Example of Boarding School Administrator for Grade 1 Students Pondok Modern Darussalam Gontor for Girls 3, Ngawi, Indonesia - Heru Saiful Anwar; Siti Zumaroh (Educan : Jurnal Pendidikan Islam, 2018)
Education is a strong foundation for a good relationship between a servant and his god, also between humans themselves. Good morality possessed by a person is not born by it self, but requires a long process that is with moral education. Gontor For Girls Campus 3 is a boarding school that always emphasizes moral education rather than teaching. Some of the many rensposible of branch have not set a good example in branch. So many of the first class who have character less good because the responsible of branch that has not given a good example in every activity. The purpose of this research to know: 1) How to implement education of morality through exemplary of first class rayon boards at Gontor For Girls Campus 3, 2) supporting factors and obstacles in the implementation of moral education through exemplary first class rayon board in Gontor For Girls Campus 3. This research is a field research that is Descriptive Qualitative, data collection techniques used are: Interview, Obsevation, Documentation. And to analyze the data, the researcher uses Miles and Hubarman methods, namely: Dokument Reduction, Dokument Presentation, and Conclusion Withdrawal and Dokument a Verification. From the analysis conducted, the researcher concludes that: Implementation of moral education through exemplary responsible of branch at class one of them that is by designing a good environment, some supporting factors and obstacles in the implementation of moral education through exemplary board members class 1, the presence of responsible of branch members in various activities in the cottage.